APPROBATION ON REGIONAL ALGORITHM SELECTION OF INVESTMENT PROJECTS PORTFOLIO - , А. В. (Municipal economy of cities (Technical science), 2013)
The approbation at the regional level, the ARC author algorithm for selecting investment projects in their portfolio, refined methods of specific points at different stages of the selection, including the composition of indicators